Effects of feeding alternative sources of crude protein on growth performance and carcass characteristics of late finishing pigs - Creager, Chloe M.; Soto, J.M.; Tokach, Michael D.; Dritz, Steven S.; DeRouchey, Joel M.; Goodband, Robert D.; Clark, Anne B. (My University, 2016)
Soybean meal (SBM) is the major protein source used in swine diets in the U.S., and it is often the standard to which other protein sources are compared. Nonetheless, other vegetable protein ingredients, such as pea protein and canola meal, can be used to replace SBM in the diet. Recent research has suggested that a significant reduction in performance and carcass characteristics occurs when late finishing pigs are fed diets below 12% CP, and that these negative impacts are not ameliorated when diets are formulated with all amino acids (AA) at or above minimum ratios relative to lysine using crystalline amino acids. Further research is needed to understand the reasons that pigs fed diets with seemingly adequate AA levels, but with less than 12% CP, have reduced performance. Therefore, the objective of this study was to determine whether SBM could be replaced with other vegetable protein sources without altering growth performance and carcass characteristics of late finishing pigs. A total of 288 pigs (DNA 600 × 241, initially 240 lb) were used in an 18-d growth study. Pigs were blocked by BW and assigned to one of 4 dietary treatments with 9 replications. Treatment 1 was a negative control containing 4.3% SBM and 10% CP. Treatment 2, 3, and 4 contained 12% CP with the protein sources being 10.7% SBM in treatment 2, 8.9% pea protein concentrate in treatment 3, and 14% canola meal in treatment 4. Overall, no differences were observed (P > 0.171) for final BW, ADG, G:F, and HCW between pigs fed 4.3% SBM, 10.7% SBM, pea protein, and canola meal diets. Pigs fed SBM with 12% CP had decreased (P = 0.017) backfat compared to pigs fed the other diets. Differences in these results compared to previous research could be due to factors such as genetic differences between pigs and potential differences in dietary AA requirements. Diets in this experiment may have been formulated over the pig’s AA requirements. These results suggest different dietary protein sources did not affect growth and carcass characteristics.
Keywords: Fall 2016